2006
DOI: 10.1525/mp.2006.24.2.147
|View full text |Cite
|
Sign up to set email alerts
|

Pitch and Timing in the Songs of Deaf Children With Cochlear Implants

Abstract: CONGENITALLY DEAF CHILDREN (5-10 years) who use cochlear implants and hearing children of comparable age sang songs from memory. Analyses of their performances revealed timing similarities in the songs of deaf and hearing children but substantial differences in pitch patterning. Whereas hearing children accurately reproduced the relative pitch patterns of the songs they sang, deaf children did not. Deaf children's pitch range was considerably smaller than that of hearing children, and their pitch changes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 34 publications
1
32
1
2
Order By: Relevance
“…Moreover, children with cochlear implants produced melodic contours with a greater pitch range than children with normal hearing. These results were surprising given that previous studies had found compressed pitch ranges in songs produced by children with cochlear implants (Nakata et al, 2006; Xu et al, 2009). …”
Section: Speech and Language Developmentcontrasting
confidence: 60%
See 1 more Smart Citation
“…Moreover, children with cochlear implants produced melodic contours with a greater pitch range than children with normal hearing. These results were surprising given that previous studies had found compressed pitch ranges in songs produced by children with cochlear implants (Nakata et al, 2006; Xu et al, 2009). …”
Section: Speech and Language Developmentcontrasting
confidence: 60%
“…Although children with cochlear implants have difficulty perceiving and producing musical melody (e.g., Nakata et al, 2006; Vongpaisal et al, 2006; Xu et al, 2009), they can discriminate pitch intervals in a nonmusical context (Vongpaisal et al, 2006). To get a sense of the potential relation between prosody and music production in children with cochlear implants, we asked the same groups of children to perform a series of melodic contours (up, down, up-down, down-up) and to sing the familiar song “Happy Birthday” (Bergeson, Chin, et al, 2010).…”
Section: Speech and Language Developmentmentioning
confidence: 99%
“…Keep in mind, however, that singing with others is possibly the most difficult of all musical tasks to achieve with any degree of accuracy, given that the implant does not provide good pitch resolution (Nakata, Trehub, Mitani, & Kanda, 2006). In considering this fact, one might question whether singing should be included in music therapy programming for preschool implant recipients.…”
Section: Music Therapy Interventions For Preschool CI Recipientsmentioning
confidence: 99%
“…For example, child CI users preserve the rhythms but not the pitch contours (i.e., patterns of rising and falling pitches) when they sing familiar songs (Nakata, Trehub, Mitani & Kanda, 2006;Xu et al, 2009). Although this pattern is mirrored, to some extent, in the song production of amusic individuals, some individuals with severe pitch perception deficits manage to produce accurate contours and intervals when singing familiar songs with words, which reveals an unexpected dissociation between perception and action (Dalla Bella, Giguère & Peretz, 2009).…”
Section: Introductionmentioning
confidence: 99%